Analisis Miskonsepsi terhadap Materi Rangkaian Listrik Searah (DC) Pada Siswa SMK Negeri Kota Kendari Menggunakan Four-Tier Diagnostic Test - Trisnawati, Agus; Erniwati, Erniwati; Eso, Rosliana (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to analyze the misconceptions of unidirectional electric circuit material in elementary school students of the city of Kendari using a four-tier test. Sampling uses a purposive sampling technique with the consideration of taking schools that have the same vocational training so that they get 4 classes from the Department of Computer and Network Engineering totaling 110 people. The population of this research is all students of SMK Negeri Kendari City. Data collection was carried out by providing a test instrument in the form of four-tier diagnostic test questions totaling 15 numbers, which were adopted from the 2018 Tami Beniarti questions and interviews. Data were analyzed using qualitative descriptive analysis to obtain a percentage of concept understanding, misconception, partial understanding, not understanding the concept and cannot be coded to students so that conclusions are obtained: (1) the average percentage of concept understanding is 12.8%, misconceptions are 24.1 %, do not understand the concept of 23.4%, understand partially by 37.5%, and cannot be coded as much as 2.2%, (2) Students' misconceptions of each sub-concept are successively electric current and potential difference (34) , 24%), electrical resistance and circuit resistance (23.94%), simple circuit analysis (17.88%), Ohm's law (21.82%), and Kirchoff's law (22.73%), (3) percentage of misconceptions among students in each vocational high school namely at SMKN 1 Kendari the percentage of misconceptions was 18.0%, for SMKN 3 Kendari the percentage of misconceptions was 19.7%, for SMKN 4 Kendari the percentage of misconceptions was 29.9%, whereas for SMKN 5 Kendari the percentage of misconceptions of 29.3%. Overall the percentage obtained for each school is of low category.